Interactive association of baseline and changes in serum uric acid on renal dysfunction among community‐dwelling persons. Issue 5 (27th December 2019) - Kawamoto, Ryuichi; Ninomiya, Daisuke; Akase, Taichi; Kikuchi, Asuka; Kumagi, Teru
Abstract: Background: Chronic kidney disease (CKD) is a major public health concern. Baseline serum uric acid (SUA) levels were independently associated with incident renal dysfunction, but whether baseline and changes in SUA produce an interactive effect on renal dysfunction remains unclear. Methods: The subjects comprised 460 men aged 68 ± 10 (mean ± standard deviation) years and 635 women aged 68 ± 9 years from a rural village. We have found participants who underwent a similar examination 3 years later, and analyzed the relationship between baseline SUA, changes in SUA, and a 3‐year follow‐up renal function evaluated by estimated glomerular filtration rate (eGFR). Results: A total of 93 (20.2%) men and 76 (12.0%) women had hyperuricemia (men: SUA ≥ 7.0 mg/dL and women: SUA ≥ 6.0 mg/dL) at baseline. Multiple regression analysis using changes in eGFR as objective variable, adjusted for risk factors as explanatory variables, showed that the baseline SUA and changes in SUA were linearly associated with changes in eGFR ( β  = －0.115, P  < .001 and β  = －0.431, P  < .001, respectively). In both normal SUA group and hyperuricemia group, changes in SUA significantly associated with changes in eGFR ( β  = －0.473, P  < .001 and β  = －0.197, P  = .009, respectively). Participants with increased SUA from normal to hyperuricemia group had greater eGFR decline over the follow‐up period, and their multivariate‐adjusted 3‐year follow‐up eGFR was significantly lower than in other groups ( P  < .001). Conclusion: Our data demonstrated that baseline and longitudinal changes in SUA were independently and interactively associated with the renal function decline among community‐dwelling persons.